Development of Reproductive Health Education Videos as an Effort to Prevent Premarital Sexual Behavior in Adolescents Aged 10-12 Years - Widiyastuti, Dyah; Nurcahyani, Lia; Mariani, Nina Nirmaya; Fitrianingsih, Yeni; Hafid, Fahmi (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Adolescents have a fairly high risk of reproductive health problems, namely premarital sexual behavior. One of the factors that causes adolescent sexual behavior is a lack of reproductive health knowledge. This study aims to analyze the effectiveness of reproductive health videos which include physical changes, healthy association, prevention of sexual harassment and the impact of promiscuity. This research method uses a quasi-experimental pre and post-test design with a sample of 30 students aged 10-12 years in three elementary schools and supported by qualitative data through interviews. Data analysis includes quantitative (univariable) and qualitative data with content analysis. The study's results obtained a p-value of 0.000 (< 0.05) so that statistically there was a significant difference between the respondents' knowledge before and after the intervention. A total of 3 respondents experienced a decrease in knowledge, 6 respondents remained, and 21 respondents increased. After participating in learning using reproductive health videos, student assessments were obtained, namely 27 students (90%) gave very good opinions, and 3 students (10%) gave good opinions about the use of videos as learning media. Conclusion: The use of reproductive health videos in elementary school students can increase knowledge about reproductive health to prevent risky sexual behaviors